2003
DOI: 10.1016/s1071-5576(02)00217-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinct functional differences of human progesterone receptors A and B on gene expression and growth regulation in two endometrial carcinoma cell lines

Abstract: To study the functional differences between the two progesterone receptor isoforms (hPRA and hPRB) in human endometrial cancer, two new endometrial carcinoma cell lines were created-one expressing hPRA and one expressing hPRB.A well-differentiated, hPR-negative Ishikawa cell line was stably transfected with either hPRA or hPRB cDNA. Transfected cells were selected, and two cell lines expressing approximately equal amounts of receptor were isolated-one expressing hPRA (PRA-14) and one expressing hPRB (PRB-59). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Microarrays have been used to investigate the molecular effects of progesterone, which is known to reduce the risk of developing endometrial cancer, and PRs are found in endometrial cancer cells (Dai et al 2002, Oehler et al 2002, Smid-Koopman et al 2003. After treatment of normal, non-transformed endometrial epithelial cells with oestradiol and the synthetic progestogen norethisterone acetate, Wnt-7a, part of the Wnt family of secreted signalling molecules, was shown to be upregulated (Oehler et al 2002).…”
Section: Expression Profile Analyses Of Endometrial Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Microarrays have been used to investigate the molecular effects of progesterone, which is known to reduce the risk of developing endometrial cancer, and PRs are found in endometrial cancer cells (Dai et al 2002, Oehler et al 2002, Smid-Koopman et al 2003. After treatment of normal, non-transformed endometrial epithelial cells with oestradiol and the synthetic progestogen norethisterone acetate, Wnt-7a, part of the Wnt family of secreted signalling molecules, was shown to be upregulated (Oehler et al 2002).…”
Section: Expression Profile Analyses Of Endometrial Cancermentioning
confidence: 99%
“…Two studies have examined the functional difference between the two human progesterone receptor (hPR) isoforms in human endometrial cancer (Dai et al 2002, Smid-Koopman et al 2003. Endometrial cancer cell lines, stably transfected with either hPRA or hPRB, were treated with progestins and differential gene expression was analysed using nylon cDNA arrays.…”
Section: Microarray Studies Of Endometriummentioning
confidence: 99%
See 1 more Smart Citation
“…3A) (38). Progesterone increased endogenous FKBP5 mRNA in IKPRB and IKPRAB cells but had no effect in parental IKLV or IKPRA cells (Fig.…”
Section: Mage-11 and Fkbp5 Increase In Early And Mid-secretorymentioning
confidence: 77%
“…Human endometrial adenocarcinoma Ishikawa cells and parental IKLV3 express low levels of PR (37) (38). Ishikawa and human cervical cancer HeLa cells were maintained in minimal essential medium (Invitrogen) containing 10% fetal bovine serum (Gemini BioProducts), 2 mM L-glutamine (Cellgro), penicillin, and streptomycin (Sigma).…”
Section: Methodsmentioning
confidence: 99%